2011
DOI: 10.1038/ejcn.2010.276
|View full text |Cite
|
Sign up to set email alerts
|

Efficient tetanus toxoid immunization on vitamin D supplementation

Abstract: Background/Objectives: Vitamin D mediates immunomodulatory functions, and its deficiency has been associated with an increased prevalence of immunological diseases. The supplementation of vitamin D might be therapeutically beneficial, for example, in lupus erythematosus patients. However, its affect on established recall immune responses is undefined. Subjects/Methods: In all, 32 individuals were randomized in a placebo controlled, double-blind setting, and received vitamin D (daily 2000 IU) for 10 weeks follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 21 publications
(38 reference statements)
5
26
0
Order By: Relevance
“…Some studies reported a lack of influence of serum VD concentrations [17,18] or VD supplementation [19,20] in response to immunization for influenza, whereas other authors reported that prostate cancer patients with higher 25(OH)D levels had higher response rates to the flu vaccine [21]. A significantly enhanced response was found to tetanus vaccination after 25(OH)D supplementation [22] or bacillus Calmette-Guérin immunization after vitamin A and D supplementation [23]. Furthermore, a study on HD patients suggested that 1,25(OH) 2 D supplementation may enhance response to flu vaccination, particularly when administered intravenously [24].…”
Section: Discussionmentioning
confidence: 88%
“…Some studies reported a lack of influence of serum VD concentrations [17,18] or VD supplementation [19,20] in response to immunization for influenza, whereas other authors reported that prostate cancer patients with higher 25(OH)D levels had higher response rates to the flu vaccine [21]. A significantly enhanced response was found to tetanus vaccination after 25(OH)D supplementation [22] or bacillus Calmette-Guérin immunization after vitamin A and D supplementation [23]. Furthermore, a study on HD patients suggested that 1,25(OH) 2 D supplementation may enhance response to flu vaccination, particularly when administered intravenously [24].…”
Section: Discussionmentioning
confidence: 88%
“…Thirty-two healthy adults who had last received tetanus/diphtheria immunization at least five years prior, and were due to receive a booster immunization, were enrolled in a double-blind intervention study in Germany [67]. Twenty subjects were randomized to receive oral vitamin D supplementation (daily 2000 IU vitamin D3) for a period of nine weeks, and the rest received placebo (neutral oil) for the same duration.…”
Section: Impact Of Vitamin D On Immune Response To Vaccinesmentioning
confidence: 99%
“…TT-specific IgG increased in both groups following booster immunization, and this was slightly higher in the vitamin D group (p=0.04). There was also a positive correlation between an increase in 25-(OH) D level following the supplementation period and change in anti-tetanus-IgG following vaccination (r=0.351, p=0.042) [67]. The immunogenicity and efficacy of tetanus toxoid vaccine in preventing tetanus is high across most age groups; however, adults with chronic renal failure have been noted to have lower antitoxin levels after tetanus toxoid vaccination than healthy controls [68-70].…”
Section: Impact Of Vitamin D On Immune Response To Vaccinesmentioning
confidence: 99%
“…Zitt et al found that VD deficiency was associated with a poor response to active hepatitis B immunisation in adult patients with chronic kidney disease, 8 whereas Heine et al found that the induction of specific tetanus toxoid immunoglobulin after booster immunisation was significantly greater in adults receiving VD supplementation than in untreated controls. 9 The results of studies of influenza vaccine are equally conflicting. Chadha et al found as vitamin D (VD) has a significant regulatory effect on innate and adaptive immunity, the aim of this prospective, randomized, single-blinded, placebo-controlled study was to measure the impact of VD administration on the immune response to trivalent influenza vaccination (TIV).…”
Section: Introductionmentioning
confidence: 99%